Vasoactive intestinal peptide is required in the maintenance of immune regulatory competency of immune regulatory monocytes - Guan, L. (Clin Exp Immunol, 2019)
Dysfunction of the immune regulatory system plays an important role in the pathogenesis of rheumatoid arthritis (RA). Vasoactive intestinal peptide (VIP) has multiple bioactivities. This study aims to investigate the role of VIP in the maintenance of the immune regulatory capacity of monocytes (Mos). Human peripheral blood samples were collected from RA patients and healthy control (HC) subjects. Mos and CD14(+) CD71(–)CD73(+)CD25(+) regulatory Mos (RegMos) were isolated from the blood samples and characterized by flow cytometry. A rat RA model was developed to test the role of VIP in the maintenance of the immune regulatory function of Mos. The results showed that RegMos of HC subjects had immune suppressive functions. RegMos of RA patients expressed less interleukin (IL)‐10 and showed an incompetent immune regulatory capacity. Serum levels of VIP were lower in RA patients, which were positively correlated with the expression of IL‐10 in RegMos. In‐vitro experiments showed that the IL‐10 mRNA decayed spontaneously in RegMos, which could be prevented by the presence of VIP in the culture. VIP suppressed the effects of tristetraprolin (TTP) on inducing IL‐10 mRNA decay in RegMos. Administration of VIP inhibited experimental RA in rats through restoring the IL‐10 expression in RegMos. RegMos have immune suppressive functions. VIP is required in maintaining IL‐10 expression in RegMos. The data suggest that VIP has translational potential in the treatment of immune disorders such as RA.